Outcomes of direct superior approach and posterolateral approach for hemiarthroplasty in the treatment of elderly patients with displaced femoral neck fractures: A comparative study - Hu, Wei; Xu, Wen-Bo; Li, Hao; Jiang, Wen-Hua; Shao, Yin-Chu; Shan, Ji-Chun; Yang, Di; Wan, De-En; Shuang, Feng (Frontiers in Surgery, 2023)
Hemiarthroplasty is a surgical choice for super-aged patients with high surgical risk and a sedentary lifestyle. Direct superior approach (DSA), as a minimally invasive modification of the posterior approach, is rarely studied in hemiarthroplasty. In this study, we aimed to compare the clinical outcomes in elderly patients with displaced femoral neck fractures undergoing hemiarthroplasty via DSA with the conventional posterolateral approach (PLA). From February 2020 to March 2021, 48 elderly patients with displaced femoral neck fractures undergoing hemiarthroplasty were retrospectively included. Among them, 24 patients (with a mean age of 84.54±2.11 years) were treated with hemiarthroplasty via DSA (DSA group), whilst 24 patients (with a mean age of 84.92±2.15 years) were treated with hemiarthroplasty via PLA (PLA group). Clinical outcomes, perioperative data, and complications were recorded. Baseline characteristics between DSA and PLA groups did not obviously differ differences including age, gender, body mass index (BMI), Garden type, American Society of Anesthesiologists (ASA) score, and hematocrit. Perioperative data showed that the incision length in the DSA group was smaller than that of the PLA group (P<0.001). However, the duration of the operation and blood loss in the DSA group were more than those of the PLA group, respectively (P<0.001). Additionally, the DSA group had less hospitalization time than the PLA group (P<0.001). Visual analogue scale (VAS) score and Harris score at postoperative 1 month in the DSA group were superior to the PLA group (P<0.001). Moreover, there were no significant differences between the two groups in the Harris score (for assessment dysfunction) 6 months after surgery (P>0.05). DSA is less invasive and has better clinical outcomes, which can allow early return to daily living activities in elderly patients with displaced femoral neck fractures undergoing hemiarthroplasty.